Retirement risks: Invasive coral on old oil platform on the Brazilian equatorial continental shelf - Braga, Marcus Davis Andrade (2021)
The objective of this study was to report, for the first time, the presence of an invasive coral (Tubastraea tagusensis) in an oil platform on the Brazilian equatorial continental shelf. This structure is located more than 1200 km north from other oil and gas structures colonized by this coral. We also discussed the retirement and decommissioning of old biofouling-encrusted oil and gas platforms (~62 platforms) from decreased production and the current oil crisis, exacerbated by the COVID-19 pandemic. This presents an ecological concern due invasive coral range expansion and potential impacts to poorly studied ecosystems such as marginal shallowwater coral reefs and mesophotic ecosystems. It is imperative that mindful risk analysis and rigorous environmental studies must precede the installation of new oil and gas platforms. In addition, decommissioning of retired structures should take into consideration marine restoration and non-indigenous species dispersal, and more specifically, Tubastraea bioinvasion